Efeito da reabilitação cardiovascular baseada em exercício na capacidade funcional, força muscular inspiratório e resultados clínicos no pré e pós-operatório de transplante cardíaco - Krainer, Isis Begot [UNIFESP] (2019)
This thesis consisted of two studies described below. Study was entitled "Inspiratory muscle weakness determines poor short-term outcomes for heart transplantation”. The aim of this study was to determine preoperative patientrelated risk factors that could adversely affects clinical course in the postoperative of patients undergoing heart transplantation. The current study concluded that an impairment of preoperative MIP was associated with poorer short-term outcomes following HT. As such, inspiratory muscle strength is an important clinical preoperative marker in patients undergoing HT. The study II is entitled “Pre- and postoperative exercise-based cardiac rehabilitation in hospitalized patients undergoing heart transplantation: a randomized controlled trial”. The aim of this study was to evaluate the effects of an inpatient cardiac rehabilitation model on functional capacity, inspiratory muscle function and clinical outcomes in patients with heart failure, started in the pre and continued at postoperative of heart transplantation. The current study concluded that pre- and postoperative exercise-based cardiac rehabilitation program in patients using stationary cycle ergometer was able to improve functional capacity and inspiratory muscle strength in end-stage heart failure patients undergoing heart transplantation.